2013
DOI: 10.1200/jco.2013.31.6_suppl.320
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of adjuvant management strategies in early-stage testicular seminoma.

Abstract: 320 Background: Acceptable post-orchiectomy management strategies for stage I seminoma include surveillance (SV), para-aortic (PA-RT) radiation therapy, dog-leg (DL-RT) or a single cycle of carboplatin (Carbo). The follow-up recommendations for each option were recently amended by the National Comprehensive Cancer Network (NCCN) in 2012. As such, surveillance imaging after treatment, a contributor to costs, was significantly scaled back. This was driven, in part, by the maturation of data from the MRC TE 19/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar issues may, however, be faced by patients, regardless of the post‐orchiectomy management as adjuvant therapy does not completely eliminate risk of relapse or the need for follow‐up in these patients. Interestingly, a recent abstract on the cost of adjuvant management in stage I seminoma has suggested that the Medicare reimbursement for surveillance in the USA ($10,643) is similar to that of other adjuvant treatments (para‐aortic RT $11,678, dog‐leg radiation $9662), with carboplatin being the lowest ($7870) . It should be noted, however, that these costs may differ in different healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Similar issues may, however, be faced by patients, regardless of the post‐orchiectomy management as adjuvant therapy does not completely eliminate risk of relapse or the need for follow‐up in these patients. Interestingly, a recent abstract on the cost of adjuvant management in stage I seminoma has suggested that the Medicare reimbursement for surveillance in the USA ($10,643) is similar to that of other adjuvant treatments (para‐aortic RT $11,678, dog‐leg radiation $9662), with carboplatin being the lowest ($7870) . It should be noted, however, that these costs may differ in different healthcare systems.…”
Section: Discussionmentioning
confidence: 99%